Investigating the Impact of Shopping Mall Brand Image Components on Visit Intention and Consumer Behavior through Attitudes towards the Mall with the Moderating Role of the Social Environment - Manian, Mona; Kheiri, Bahram; Bameni Moghadam , Mohammad (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: This study aims to investigate the impact of shopping mall brand image components on visit intention and consumer behavior through attitudes towards the mall, with the moderating role of the social environment.Methodology:  The research method is applied, survey-descriptive, and the data collection tool is a questionnaire. The statistical population of this research consists of female customers of shopping malls in Tehran, with a simple random sampling method and a statistical sample of 618 individuals. Data analysis was conducted using SPSS and Smart PLS software.Findings:  The results confirm the impact of brand image on consumer attitudes towards shopping malls, the impact of consumer attitudes towards shopping malls on visit intention and consumer behavior, and the impact of visit intention on consumer behavior.Conclusion: Therefore, marketers and brand managers can adopt appropriate strategies in each of these areas to create a strong brand image in customers' minds. Companies must study literature, previous research results, and provide multiple pieces of evidence on the relationship between the hypotheses' variables, considering these results academically. The necessity and reason for repeating research lie in the discrepancies found by the researcher, making further studies on rejected hypotheses feasible.